Calculations of electron-impact ionisation of Fe25+ and Fe24+. (23rd August 2016) - Fursa, Dmitry V; Bostock, Christopher J; Bray, Igor; Fontes, Christopher J
Abstract: Electron-impact ionisation cross sections for the hydrogen- and helium-like ions of iron are calculated. The convergent close-coupling and distorted-wave methods in the relativistic and nonrelativistic formulations are used. The cross sections are in very good agreement with the results of the corresponding methods, with the relativistic formulation establishing the benchmarks to few percent accuracy.